Converged memory institutions : combining public library and cultural resources to achieve an information and social commons - Robinson, Leith Therese Kelly (Curtin University, 2012)
The 21st Century’s living and working environment has been transformed by technological advancements, and affected by the trends of globalisation, financial restriction and citizen participation. In response, many information and cultural organisations [memory institutions] such as galleries, libraries, archives and museums are converging aspects of their collections, services and management. This convergence may be physical or virtual, and the subsequent evolution of operations has implications for sites, staff and users. This research explores the theory and practice of convergence as it is impacting upon a particular group and domain of memory institutions, namely public libraries in Western Australia. In addition there is a focus on the interrelationship of convergence with professional and institutional identity, and with the emerging concept of the information and social commons.The research consists of two principal forms of data collection. Firstly, a survey canvassing the opinions of Western Australian public librarians; and secondly, case studies undertaken in four Western Australian local government areas.The findings from these two methods are used to form recommendations for the best operation of a converged memory institution (CMI). Convergence is suggested as particularly appropriate at the local level, and libraries are recommended as the anchoring domain in a CMI, to maximise social capital and form a community hub. This thesis acknowledges the challenging and complex nature of convergence, but argues that as memory institutions converge they improve the delivery of information and cultural services via the optimisation of collectionutility and process efficiency. Thus greater information and social benefits are achieved, and the value and relevance of the collecting sector is reinforced.